ANALISIS NILAI-NILAI KARAKTER DALAM EKSTRAKURIKULER KARAWITAN DI SDN SUNGGINGWARNO 01 KABUPATEN PATI - Novita Ramadani Purnama Sari; Rofian; Wawan Priyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study is motivated by character values in students who tend to experience a decline and the loss of student interest in traditional Javanese arts, especially karawitan. The purpose of this study is to analyze character values and the application of character values in extracurricular kara witan activities at SDN Sunggingwarno 01 Pati Regency. This research used a qualitative method with a descriptive approach. Data collection techniques used observation, interviews, and documentation. The results of this study indicate that the character values contained in extracurricular kara witan are religious, tolerance, discipline, hard work, independence, democracy, love for the country, friendly/communicative, peace-loving, environmental care, social care, and responsibility. The application of these character values is by the expected indicators of character values.